PENGARUSUTAMAAN GENDER (PUG) DALAM TANTANGAN BUDAYA PATRIARKI - Henny Yusalia (Wardah, 2014)
The term gender mainstreaming (PUG) refers to the understanding that the concept of gender should be encouraged to be understood by the public. Which emphasizes the aspect of gender equality and social justice role, must be maximized, so that domination and "oppression" of women can be minimized. PUG concept inevitably be faced with socio-cultural and political realities of society, which is still very dominant with a patriarchal culture. The power of patriarchal culture (male power) already attached so strong in the community, even the legitimacy of the woman. This article also wants to raise the issue of the implementation of gender mainstreaming in the context of the strong theoretical patriarchy. This theoretical study shows that the various elements of society, patriarchal culture is still maintained and there is justification to continue. Eventhough, it also related to religious beliefs and traditions that take place. On the other side of a patriarchal culture has also strengthened with the emergence of popular culture which emphasizes aspects of the material, so that women often used as commodities. This further reinforces the patriarchal culture, as well as challenges for PUG.